Analisis Tren Nilai Tukar Mata Uang Rupiah Indonesia (IDR) terhadap Ringgit Malaysia (MYR) - Anwar, Mukhlis Kaspul (Ecobuss, 2025)
This study aims to analyze the trend and forecast the exchange rate of IDR against MYR by comparing two trend models, namely the linear and quadratic trend models. The analysis results show a downward trend in the IDR to MYR exchange rate during the observed period. From the comparison of both models, the quadratic trend model proves to be more effective in depicting the exchange rate movement pattern, as it yields a smaller MAPE value, indicating higher prediction accuracy. The quadratic model is better at capturing complex fluctuations of the exchange rate, providing better results than the linear model. Therefore, the quadratic trend model is more suitable for modeling the downward trend in the IDR to MYR exchange rate.